Pengaruh Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Kantor Pengadilan Agama Jakarta Timur - Vikko Trioda; Dedy Syahyuni; Lady Diana Warpindyastuti (Jurnal Publikasi Ilmu Manajemen, 2025)
Human resources refer to the innate abilities possessed by humans to fulfill their functions as social creatures and organize themselves effectively in order to achieve success and prosperity in life. The aim of this research is to assess the influence of work motivation and organizational commitment on employee performance at the East Jakarta Religious Court Office. The research used was a quantitative statistical method with a population of 69 employees. Data analysis techniques use instrument tests, classical assumptions, normality, muticolinearity, hetroscedasticity, linearity, and multiple linear regression analysis. The results of this research show the influence of work motivation on performance, namely t count of 7.810 > t table of 1.997, the magnitude of the influence of work motivation on employee performance is 0.579 (57.9%). There is an influence of Organizational Commitment on Employee Performance, namely t count 3.070 > t table 1.997), the magnitude of the influence of Organizational Commitment on Employee Performance is 0.291 (29.1%). Work Motivation and Organizational Commitment have a significant influence on Employee Performance. The contribution of the influence of the Work Motivation and Organizational Commitment variables to employee performance is 0.632 or 63.2%, while the remaining 0.368 or (36.8%) is influenced by other factors.